Volume 7: Dynamic Systems and Control; Mechatronics and Intelligent Machines, Parts a and B 2011
DOI: 10.1115/imece2011-65867
|View full text |Cite
|
Sign up to set email alerts
|

A New Field Unbalance Estimation Method for Flexible Rotors

Abstract: Current field unbalance estimation methods regards “flexible rotors with lumped mass” as the main research object, and most of them need a stop running to take trial weights. Due to its test speed closing to the critical speed, the process of balance is really complicated and dangerous. This paper concerns rotors which unbalance state shows a continuous spatial distribution. Firstly, a dynamic finite element (FE) model of the rotor system is built, the inherent relations and differences between the dynamics tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Deepthikumar et al [30] have replaced the transfer matrix with the influence coefficient matrix to achieve the dynamic balance of the flexible rotor. Zhang et al [31,32] have found and proved that the two are equivalent by studying the relationship between the rotor dynamics transfer function and the influence coefficient and completing the dynamic balance of the flexible rotor through the transfer function.…”
Section: Introductionmentioning
confidence: 99%
“…Deepthikumar et al [30] have replaced the transfer matrix with the influence coefficient matrix to achieve the dynamic balance of the flexible rotor. Zhang et al [31,32] have found and proved that the two are equivalent by studying the relationship between the rotor dynamics transfer function and the influence coefficient and completing the dynamic balance of the flexible rotor through the transfer function.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the most of the spindle dynamic balance regulator using trial weights method [3], however, the mistake trial weights will due to the violent vibration. The situation of amplitude change of spindle vibration signal is able to warn the mistake trial weights, and avoid the fault of the running spindle [4,5]. The signal of the spindle dynamic balance regulator online adjustment process has strong nonstationarity, which could not process with traditional signal processing methods.…”
Section: Introductionmentioning
confidence: 99%